Prevalence of pericoronitis in impacted mandibular third molar: A Retrospective analysis of 86,000 patient records over nine months - REZVI, FATHIMA BAREERA; BALASUBRAMANIAM, ARTHI; CHAUDHARY, MANJARI (The journal of contemporary issues in business and government, 2020)
Third molar impaction has become an important clinical issue.The impacted teeth may have many pathologies such as pericoronitis, periodontitis, root resorption, space infection and coronal and root caries. The study was aimed to find the prevalence of pericoronitis in impacted mandibular third molars. This retrospective study was conducted using records of patients visited private dental college. A total of 102 case records with information on impacted mandibular third molar and pericoronitis were retrieved. Data collected from their records were entered and subjected to statistical analysis. Descriptive statistics and Chi-square association was done to find the prevalence and association between impacted mandibular third molars and pericoronitis. Out of 102 subjects, 87.3% of patients with impacted mandibular third molars had pericoronitis and it was more in males (47.1%) when compared to females (40.2%). It was more prevalent in the age group of 21-30 (57.8%) and in the left mandibular third molar, 38 (51.0%) when compared to the right, 48 (36.3%). There was no significant association of pericoronitis with age, gender, tooth number (p>0.05).Within the limits of the study majority of patients with impacted mandibular third molars had pericoronitis and it was more prevalent in males and in the age group of 17-26 years. Prevalence of pericoronitis was high in the impacted left mandibular third molar compared to the impacted right mandibular third molar.